Penerapan E-Book Fisika Berbasis Saintifik Untuk Meningkatkan Motivasi Belajar Siswa Kelas VIII SMP Negeri 11 Lubuklinggau - Jenny Irwansyah; Ovilia Putri Utami Gumay; Wahyu Arini (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The aim of this research is to increase students' motivation to learn physics after participating in learning activities using scientific-based physics E-books. This research is development research using the 4D model. The subjects of this research included students in class VIII.1 of SMP Negeri 11 Lubuklinggau. The data collection technique was carried out using a learning motivation questionnaire. The assessment of student learning motivation significantly increased with the results before using the media only getting a score percentage of 49%, while the results of the student learning motivation questionnaire after using learning media got a score percentage of 86% in the very high category. Based on the results of the analysis, it can be concluded that the learning media is effective in increasing students' learning motivation